2011
DOI: 10.1371/journal.pone.0016105
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cell Elongation to the Biofilm Formation of Pseudomonas aeruginosa during Anaerobic Respiration

Abstract: Pseudomonas aeruginosa, a gram-negative bacterium of clinical importance, forms more robust biofilm during anaerobic respiration, a mode of growth presumed to occur in abnormally thickened mucus layer lining the cystic fibrosis (CF) patient airway. However, molecular basis behind this anaerobiosis-triggered robust biofilm formation is not clearly defined yet. Here, we identified a morphological change naturally accompanied by anaerobic respiration in P. aeruginosa and investigated its effect on the biofilm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 50 publications
14
107
1
1
Order By: Relevance
“…1B), suggesting that these respiratory enzymes have a physiological role under anoxic denitrifying conditions. In a study by Yoon et al, it was demonstrated that P. aeruginosa PAO1 elongates and aggregates in anoxic planktonic shaking cultures (26). Similar phenomena were observed in the WT by DIC observation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…1B), suggesting that these respiratory enzymes have a physiological role under anoxic denitrifying conditions. In a study by Yoon et al, it was demonstrated that P. aeruginosa PAO1 elongates and aggregates in anoxic planktonic shaking cultures (26). Similar phenomena were observed in the WT by DIC observation.…”
Section: Resultsmentioning
confidence: 54%
“…Under anoxic conditions where NO 3 Ϫ is present, P. aeruginosa can grow through denitrification, in which NO 3 Ϫ is reduced subsequently to NO 2 Ϫ , NO, N 2 O, and, finally, to N 2 (3). Cell elongation under anoxic conditions is attributed to the accumulation of NO that is produced during such a process (26). Our data showed that cbb 3 oxidases affect cell morphology; hence, the effect of cbb 3 oxidases on the denitrification process was investigated.…”
Section: Resultsmentioning
confidence: 78%
“…P. aeruginosa laboratory strains (PAO1, PA14, PAK, and FRD1) and pneumonia patient isolates have been previously described (25,47,57,58). The PAO1 ⌬lasB mutant was purchased from a P. aeruginosa transposon mutant library (www.genome.washington.edu /UWGC/pseudomonas) and sequence verified.…”
Section: Methodsmentioning
confidence: 99%
“…As the biofilm evolves, it undergoes cellular differentiation and multicellular morphogenesis. In select bacteria, there is stratification of cellular phenotypes and the development of an often complex multicellular architecture (110)(111)(112)(113). In Pseudomonas aeruginosa, cells differentiate from a round to an elongated phenotype (113), and they exhibit changes in physiology, gene transcription, and protein synthesis (81,(114)(115)(116).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%
“…In select bacteria, there is stratification of cellular phenotypes and the development of an often complex multicellular architecture (110)(111)(112)(113). In Pseudomonas aeruginosa, cells differentiate from a round to an elongated phenotype (113), and they exhibit changes in physiology, gene transcription, and protein synthesis (81,(114)(115)(116). One of the most dramatic phenotypic transitions is that of E. coli (80,86) and P. aeruginosa (81,117,118).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%